2006
DOI: 10.1177/1088767905285510
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Victim Race and Gender on Sentencing Outcomes in Capital Murder Trials

Abstract: This study extends previous research on the interactive effects of victim race and gender on death sentence outcomes reported by Williams and Holcomb (2004). They report an interactive effect between victim race and victim gender on Ohio death sentencing outcomes, such that killers of White women are especially at risk of receiving death sentences. The study here seeks to determine if the Williams and Holcomb finding holds for a sample of murder cases in North Carolina for which the state sought the death pena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 11 publications
5
53
1
1
Order By: Relevance
“…To our knowledge, only six studies to date have specifically focused on the relationship between victim sex and capital sentencing outcomes (Gillespie et al, 2013;Holcomb et al, 2004;Richards et al, 2014;Stauffer et al, 2006;Williams and Holcomb, 2004;Williams et al, 2007). Results from this body of work have demonstrated evidence that is generally supportive of a female victim effect -at least at some times, under some circumstances -but that victim sex effects are often mediated and/or moderated by other factors.…”
Section: Prior Victim Sex and Death Penalty Researchmentioning
confidence: 89%
See 2 more Smart Citations
“…To our knowledge, only six studies to date have specifically focused on the relationship between victim sex and capital sentencing outcomes (Gillespie et al, 2013;Holcomb et al, 2004;Richards et al, 2014;Stauffer et al, 2006;Williams and Holcomb, 2004;Williams et al, 2007). Results from this body of work have demonstrated evidence that is generally supportive of a female victim effect -at least at some times, under some circumstances -but that victim sex effects are often mediated and/or moderated by other factors.…”
Section: Prior Victim Sex and Death Penalty Researchmentioning
confidence: 89%
“…Again, while cases with female victims and White victims were significantly more likely to receive the death penalty compared with cases involving male victims or non-White victims, cases with White female victims were associated with the highest odds of receiving the death penalty compared to the other victim race/sex compositions. Stauffer et al (2006) extended Williams and Holcomb's (2004) and Holcomb et al's (2004) research by examining victim sex, victim race, the interaction of victim sex and race, and several hypothesized mediating variables using a near population of North Carolina capital cases (n = 953) from 1979 to 2002. Their models included: (1) a model testing for the direct effect of victim sex and race, (2) a model testing for victim sex-race interaction effects, and (3) a model testing for effects of hypothesized mediating variables.…”
Section: Prior Victim Sex and Death Penalty Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…However, studies of crime reporting and policing and studies involving other stratification variables such as age, sex, and socioeconomic status produce mixed or negative results (see, for example, Baumer, 2002;Black, 1970;Braithwaite and Biles, 1980;Chappell and Maggard, 2007;D'Alessio and Stolzenberg, 2003;Doyle and Luckenbill, 1991;Eitle et al, 2005;Furlong and Mehay, 1981;Gaines, 2006;Gottfredson and Hindelang, 1979;Häkkänen and Laajasalo, 2006;Mastrofski et al,2002;Stauffer et al, 2006;Stolzenberg et al, 2004;Wells et al, 2006;Williams and Holcomb, 2004).…”
Section: Stratificationmentioning
confidence: 96%
“…Results from an initial logistic regression analysis indicated that the coefficient for cases involving Black male victims was statistically different from cases involving White female victims (Stauffer et al, 2006). Cases involving Black male victims were only about half as likely to receive a death sentence.…”
Section: The Interaction Of Victim Race and Gender On Death Sentencinmentioning
confidence: 98%